METTL3-mediated m6A is required for murine oocyte maturation and maternal-to-zygotic transition. Issue 4 (16th February 2020) - Sui, Xuesong; Hu, Yue; Ren, Chao; Cao, Qiqi; Zhou, Shuai; Cao, Yumeng; Li, Mingrui; Shu, Wenjie; Huo, Ran
ABSTRACT: N 6 -methyladenosine (m 6 A) is the most prevalent epigenetic modification of messenger RNA (mRNA) in higher eukaryotes; this modification is mainly catalyzed by a methyltransferase complex including methyltransferase-like 3 (METTL3) as a key factor. Although m 6 A modification has been proven to play an essential role in diverse biological processes, our knowledge of Mettl3 is still limited because Mettl3 mutations are lethal to embryos in both mammals and plants. In this study, we knocked down Mettl3 by microinjection of its specific short interfering RNAs (siRNAs) or morpholino into fully grown germinal vesicle (GV) oocytes. As a result, we demonstrated that knocking down Mettl3 in female germ cells severely inhibited oocyte maturation by decreasing mRNA translation efficiency and led to defects in the maternal-to-zygotic transition, probably due to its interference in disrupting mRNA degradation. The discovery from this study suggests that the reversible m 6 A modification has vital functions in mammalian oocyte maturation and pre-implantation embryonic development processes.